XX 5 Mesto Zensk : International Festival of Contemporary Arts Ljubljana. - Bakker, Marian; Junc, Rok; Kostic, Aleksandar D.; Lee, Sadie; Paulus, Tom; Skafar, Vlado; Spolar, Nada Kirn; Van Daele, Koen; Weiss, Maja; Zavirsek, Darja (Ljubljana : International Festival of Contemporary Arts, 1999)
Crispell, Marilyn ; Lee, Sadie ; Wilson, Martha ; Image/Imagination, The Lesbian ; Savic, Sonja ; Gosfield, Annie ; Sherman, Cindy ; Lyovsky, Noëmie ; Braidotti, Rosi ; Asher, Meira ; Mesko, Nina ; Cabro, Valentina ; Hilal, Suraya ; Mutamassik, DJ
XX 5 : City of Women, International Festival of Contemporary Arts, Ljubljana, 13. - 20.10.1999
Engels
boek